2014
DOI: 10.1021/jp507008x
|View full text |Cite
|
Sign up to set email alerts
|

Multisite Ion Model in Concentrated Solutions of Divalent Cations (MgCl2 and CaCl2): Osmotic Pressure Calculations

Abstract: Accurate force field parameters for ions are essential for meaningful simulation studies of proteins and nucleic acids. Currently accepted models of ions, especially for divalent ions, do not necessarily reproduce the right physiological behavior of Ca2+ and Mg2+ ions. Saxena and Sept (J. Chem. Theor. Comput.2013, 9, 3538–3542) described a model, called the multisite-ion model, where instead of treating the ions as an isolated sphere, the charge was split into multiple sites with partial charge. This model pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 68 publications
2
74
0
Order By: Relevance
“…In the work of Zhu et al [57], the ion association in MgCl 2 solution is much less obviously than that in CaCl 2 solution. Compared with the results of Zhu et al, the situation is reversed, which also agrees with the MD results of Saxena [25]. Since the constraint on the first hydration shell of Mg 2 + is strong, 0.25 ns may be not enough for relaxation, and thus the ion association was underestimated in the work of Zhu et al B3LYP/aVDZ results of MgCl 2 (H 2 O) n (n = 5-10) clusters show that ion associated species are slightly less favourable.…”
Section: Ion Association At Various Pressuressupporting
confidence: 89%
See 1 more Smart Citation
“…In the work of Zhu et al [57], the ion association in MgCl 2 solution is much less obviously than that in CaCl 2 solution. Compared with the results of Zhu et al, the situation is reversed, which also agrees with the MD results of Saxena [25]. Since the constraint on the first hydration shell of Mg 2 + is strong, 0.25 ns may be not enough for relaxation, and thus the ion association was underestimated in the work of Zhu et al B3LYP/aVDZ results of MgCl 2 (H 2 O) n (n = 5-10) clusters show that ion associated species are slightly less favourable.…”
Section: Ion Association At Various Pressuressupporting
confidence: 89%
“…The recent work of Jungwirth et al also indicated the formation of ion-associated species in 4.0 mol/kg CaCl 2 aqueous solution using classical MD simulations [24]. Whereas, osmotic pressure calculations of Sasena et al [25] exhibited SSIP with double Cl − dissociated (SSIP/d, [Ca(H 2 O) 6 Cl 2 ] 0 ,) structures instead of CIP structures exist in 0.1-3.0 mol/kg CaCl 2 electrolyte solutions. It seems that CIP structures cannot be easily detected even in concentrated CaCl 2 aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…FFs determined by these means have frequently been unable to satisfactorily predict more complex and composition-dependent thermodynamic properties, and thus the composition dependence of solution chemical potentials [44], and the osmotic pressure, [35,24,34,56], ˘, have recently been used as alternative approaches to fit FF parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Explicit solvent simulations appear to underpredict Γ 2+ , possibly because K + can dehydrate too easily [41] and drive away Mg 2+ . Many ion parameters have been proposed for explicit solvent simulation [4245]. The excess Mg 2+ is a sensitive measure of RNA electrostatics that may be useful in future calibration of explicit solvent ion parameters.…”
mentioning
confidence: 99%